IMPROVING HIGH SCHOOL STUDENT’S KNOWLEDGE ABOUT COVID-19 AND ITS VACCINATIONS - Laura Navika Yamani; Erni Astutik; Siti Qamariyah Khairunisa; Yasmin Nihayatun Nadzifah; Novia Indah Puspitasari (Universitas Airlangga, 2022)
Introduction: COVID-19 continues to be a global problem. Surabaya is among the cities hit by COVID-19. Lack of information and awareness of COVID-19 and its vaccination in teenagers might have impacted their preventative behavior and belief in COVID-19 vaccination. This study examined differences in high school students' understanding of COVID-19 and its vaccination before and after the intervention. Methods: The quasi-experimental design was utilized in this study, which took place between September and December of 2021. PowerPoint materials (webinar), videos, and pocketbooks about COVID-19 and its vaccination were the educational community initiatives. Students in grades 10-12 at SMA 4 Muhammadiyah Surabaya, MA Mamba'ul Hisan Gresik, and SMA Negeri 1 Sidoarjo participated in the study, and 160 students completed the pre-test and post-test. The study variables were knowledge, student characteristics (gender, age, class, and school origin), and parental characteristics (age, education, and occupation). The paired t-test was used to evaluate the univariable and bivariable data. Results: With an average pre-test value of 7.09 and a post-test value of 7.94, there was a difference of high school students' understanding of COVID-19 before and after the intervention (p < 0.001). Furthermore, there was also a difference of knowledge about COVID-19 vaccination (p < 0.001), with an average pre-test value of 5.87 and a post-test value of 7.03. Conclusion: There are considerable differences in students' knowledge of COVID-19 disease and its vaccination before and after the intervention. In order to prevent COVID-19, community service activities involving the distribution of information (webinars), videos, and pocketbooks could help them gain more knowledge.